THU0453 What is Hidden Under the Palindromic Rheumatism Umbrella?. (23rd January 2014) - Andrei, C. M.; Pamfilie, O.; Felea, I.; Popov, H.; Ghib, L.; Damian, L.; Simon, S.-P.; Rednic, S.
Abstract : Background: Palindromic rheumatism (PR) is a clinical entity, characterized by multiple, recurrent, transient episodes of arthritis and periarthritis, lasting from hours to days, with spontaneous resolution and symptoms free periods between attacks. It is well known that rheumatoid arthritis (RA), microstatline arthritides (MA) and some autoinflammatory syndromes (AIS) can have a PR onset, but there are few data about other definite diseases which have an articular involvement with a PR pattern. Objectives: Identification of other diseases (excepting those mentioned above) in which the onset and articular manifestations had a PR pattern during follow-up period. Methods: An observational prospective study for a 3 years period including patients from Rheumatology Department Cluj-Napoca. Results: Using clinical and paraclinical parameters, 8 patients with PR have been identified belonging to definite entities (excepting RA, MA and AIS) – 7 females and 1 male, with a mean age of 41.5 years. The final diagnoses were: one male with Crohn's disease, one case with primary biliary cirrhosis (PBC), one case with type I autoimmune hepatitis (AIH), one with Still's disease, one with villonodular synovitis (VNS) of knee and 3 patients with relapsing polychondritis. Mean duration from onset to diagnosis was one month in the case of autoimmune hepatitis and Still's disease, one year in the case of VNS and 2.7 years respectively in the rest of cases. In all patients, the arthritis episode lasted 24-48 hours, with spontaneous resolution, evanescent and migratory pattern, accompanied by periarticular erythema and swelling. The affected joints were: knees, ankles, elbows, metacarpophalangeal, chondrocostal (asymmetrically). Systemic manifestations included fever and weight loss in 4 subjects. Inflammatory syndrome was pronounced in all cases during articular attacks, excepting the patient with VNS. Rheumatoid factor and anti CCP antibodies were negative in all cases and antinuclear antibodies (ANA) were positive only in autoimmune hepatitis. There was no radiographic joint damage, but ultrasound evaluation (done in three subjects) revealed soft tissue swelling in all of them, synovitis in one case and infrapatellar bursitis in another one. Surgical treatment stopped the disease evolution in VNS, one case with relapsing polychondritis progressed to arthritis mutilans. The rest of the patients were managed by applying the background therapy of the underlying disease, with no further relapses, excepting the case with Crohn's disease. Conclusions: The current publications provide more and more data to sustain the progession of PR to RA, but to our knowledge, there were no cases of AIH or PBC to have an onset of PR pattern. References: Powell A, Davis P, Jones N, Russel AS. Palindromic rheumatism is a common disease: comparison of new-onset palindromic rheumatism compared to new-onset rheumatoid arthritis in a 2-year cohort of patients. J Rheumatol 2008 Jun; 35(6):992-4. Sanmarti R, Cañete JD, Salvador G. Palindromic rheumatism and other relapsing arthritis. Best Pract Res Clin Rheumatol 2004;18:647–61. Pasero G, Barbieri P. Palindromic rheumatism: you just have to think about it. Clin Exp Rheumatol 1986;4:197–9. Disclosure of Interest: None Declared